2013
DOI: 10.3109/13880209.2013.837074
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neuroprotective effects of extract and fractions fromAgarum clathratumagainst experimentally induced transient cerebral ischemic damage

Abstract: Objective: We investigated the neuroprotective effects of crude-extract, ethyl acetate (EA)-, n-butanol (BU)-, dichloromethane (DCM)-and n-hexane (Hx)-fractions from A. clathratum on ischemic damage in the gerbil hippocampal CA1 region (CA1) after 5 min of transient cerebral ischemia. Materials and methods: Agarum clathratum was collected in Kangwon province (South Korea) and treated with 95% ethanol. The ethanol extract was suspended in distilled water and subjected to a series of partitions with EA, BU, DCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…We found a significant loss of pyramidal neurons in stratum pyramidale of the ischemic CA1 region in the ischemia-groups 5 days after ischemia-reperfusion using NeuN immunohistochemistry and F-J B histofluorescence staining. This outcome is consistent with our previous studies using the same animal model [21,29,30].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found a significant loss of pyramidal neurons in stratum pyramidale of the ischemic CA1 region in the ischemia-groups 5 days after ischemia-reperfusion using NeuN immunohistochemistry and F-J B histofluorescence staining. This outcome is consistent with our previous studies using the same animal model [21,29,30].…”
Section: Discussionsupporting
confidence: 94%
“…To examine neuronal damage in the hippocampal CA1 region after transient cerebral ischemia in each group, using NeuN immunohistochemistry according to our previous method [21], the sections were sequentially treated with 0.3 % hydrogen peroxide (H 2 O 2 ) in PBS for 30 min and 10 % normal goat serum in 0.05 M PBS for 30 min. The sections were next incubated with diluted mouse antiNeuN (a neuron-specific soluble nuclear antigen) (diluted 1:1000, Chemicon International, Temecula, CA) overnight at 4°C.…”
Section: Immunohistochemistry For Neunmentioning
confidence: 99%
“…This result corresponds to findings of previous studies (23,32,33). In addition, it was identified that the oral pre-treatment of 200 mg/kg CIL to the gerbils protected CA1 pyramidal cells (~67% of the sham-operated gerbils) from 5 min of transient cerebral ischemia; this finding was identical to a previous study of the authors (22).…”
Section: Discussionsupporting
confidence: 93%
“…For example, extract from Dictyopteris divaricate, belonging to the Dictyotaceae family, displays protective effect via regulating expressions of apoptosis-related proteins in an oxygen and glucose deprivation/reperfusion cell culture model using human neuroblastoma cells [16]. Additionally, extract and fractions from Agarum clathratum, a family of Agaraceae, show neuroprotective effects by reducing reactive astrogliosis and microgliosis following TFI in gerbils [17]. In particular, Kang et al (2012) reported that fucoidan, a sulfated polysaccharide derived from brown seaweeds, displayed neuroprotective effects in a rat model of lipopolysaccharide-accelerated ischemic injury following middle cerebral artery occlusion through inhibition of cytokine expression and neutrophil infiltration [18].…”
Section: Discussionmentioning
confidence: 99%